Haemodynamics of hypertonic saline and dexamethasone administration during endotoxic shock in buffalo calves - GHUMAN, G S; SINGH, D V (The Indian Journal of Animal Sciences, 2011)
Endotoxic shock was produced in 5 apparently healthy buffalo calves aged between 4 months to 1 year, by i/v infusion of Escherichia coli endotoxin @ 5 μg/kg BW/h for 3h. The endotoxin infusion lead to the development of clinical symptoms of restlessness, respiratory distress, diarrhoea and profuse salivation. The animals closed their eyes and struggled intermittently with the progression of the endotoxin infusion. A highly significant fall in mean systolic, diastolic, pulse, mean arterial pressure (MAP), central venous pressure (CVP), hematocrit and hemoglobin was observed till the end of endotoxin infusion. All the endotoxemic buffalo calves were infused i/v hypertonic saline solution (7.2% NaCl acq.) @4 ml/kg BW in 6.5 min followed by dexamethasone @ 4 mg/kg BW as one time infusion.While CVP returned to normal levels after treatment but at the end of the observation period, it was slightly below normal. The body temperature varied nonsignificantly during and after endotoxin infusion and the treatment but the respiratory rate increased significantly at 6 and 7 h of observation. The infusion of hypertonic saline and dexamethasone effectively restore the various hemodynamic parameters to normal pre-infusion values although respiration rate remained unaffected.